2021
DOI: 10.3390/medicina57010078
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Utility of Circulating Growth Factors in Aortic Valve Stenosis: A Pilot Study

Abstract: Background and Objectives: Aortic valve stenosis (AS) develops with a pronounced local inflammatory response, where a variety of growth factors are involved in the process, and may have a pro-inflammatory and anti-inflammatory effect. The aim of our study was to elucidate whether circulating growth factors: growth differentiation factor 15 (GDF-15), angiopoietin-2 (Ang-2), vascular endothelial growth factor A (VEGF-A), fibroblast growth factor 2 (FGF-2), and fibroblast growth factor 21 (FGF-21) could be propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…In another previous study, we also found that plasma concentrations of several growth factors are increased in AS patients [28]. Our results in this study show that not only TRX1, but also proinflammatory biomarkers, namely chemerin, GDF-15, VEGF-A, and FGF-2, and the anti-inflammation biomarker FGF-21 have significant correlations regarding AS severity degrees.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In another previous study, we also found that plasma concentrations of several growth factors are increased in AS patients [28]. Our results in this study show that not only TRX1, but also proinflammatory biomarkers, namely chemerin, GDF-15, VEGF-A, and FGF-2, and the anti-inflammation biomarker FGF-21 have significant correlations regarding AS severity degrees.…”
Section: Discussionsupporting
confidence: 80%
“…Our studies, which included testing a broad spectrum of cytokines, growth factors, and oxidative stress-related biomarkers, suggest that GDF-15 and chemerin most effectively reflect the early stage of AS [21,28], and TRX1 joined this study.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Inflammation and tissue remodeling involving numerous growth factors contribute to AVS pathogenesis, and circulating growth factors have been recently proposed as potential biomarkers for AVS 11 . Angiopoietin like-2 (ANGPTL2) is a circulating proinflammatory and pro-angiogenic protein 12 , a member of the large family of angiopoietin-like glycoproteins (Angptls), a family of eight (angptl1-8) members that play key roles in various biological and pathological processes.…”
mentioning
confidence: 99%
“…Previously, predictive ability for cardiovascular events, all-cause mortality and cardiovascular mortality was demonstrated in HF patients [138]. GDF-15 levels were found to be sufficiently elevated in patients with mild to severe AS compared to patients without this disease [139]. Moreover, a strong association of GDF-15 levels with the degree of aortic stenosis was found [140].…”
Section: Biomarkersmentioning
confidence: 96%